ISOLASI CEMARAN ENTEROBAKTER PADA AIR TANAH GAMBUT DI WILAYAH KUBU RAYA - Sugito Sugito (Meditory : The Journal of Medical Laboratory, 2020)
Background. Peat soil is a type of soil that is formed from the accumulation of half-decayed plant debris. High organic matter content and some minerals with a thickness of approximately 50 cm. The high content of organic matter in peat soils is thought to be one of the factors that play an important role in supporting the process of adaptation of functional microbes. This is because the availability of organic materials needed by functional microbes for growth and metabolism is met.Method. The sampling method used is purposive sampling. Peat water samples were taken in a composite manner from 2 locations with 10 points on the right and 10 points on the creek flow with a distance of about 10 meters at each point with a trench flow length of 100 meters. Samples were taken in the morning, afternoon, and evening from each point then the inspection was carried out at the Polytechnic Laboratory of the Ministry of Health Pontianak.Results. The distribution of Enterobacter in peat soil water samples taken in the morning, afternoon, the evening is still high with based on identification obtained an average percentage of bacteria Klebsiella Pneumonia 100%, Shigella Dysentery 100%, Proteus Vulgaris 80%, Escherichia Coli 70% and Salmonella 70% and Salmonella Typhi 20%. The coagulation test to determine the type or species of a bacterium from the Enterobacter group is carried out with an antisera test.Concl. There is a relationship between morning water samples with afternoon and evening. Based on the Kendall Tau test, the value of the p-value smaller than α (0.05) is 0.009.